Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/tea.3660281004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of applied and theoretical knowledge of concepts based on the particulate nature of matter

Abstract: This study compares 183 high school chemistry students' applied and theoretical knowledge of selected concepts based on the particulate theory. The concepts are dissolution, diffusion, effusion, and states of matter. A two‐form instrument called the Physical Changes Concepts Test (PCCT) was developed for this study. The application form measures students' knowlege using everyday language. The theoretical form measures students' knowledge using scientific language. Students' formal reasoning ability was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
18

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 17 publications
1
72
0
18
Order By: Relevance
“…Although atomic and molecular structures and behaviours explain a plethora of chemical and lot of physical phenomena, students have difficulties understanding many concepts related to gases, liquids and solids (Krnel et al, 1998;Mullet and Gervais, 1990;Lee et al, 1993;BouJaoude, 1991;Domenech et al, 1993;Novick and Nussbaum, 1978;Benson et al, 1993;Krnel, 1994;Pereira and Pestana, 1991) and quantum concepts (Styer, 1996;Petri and Niedderer, 1998;Griffiths and Preston, 1992). For example, some drawings of high-school students show different forms of particles for different states of matter: gas molecules are round, molecules of liquids have irregular forms, molecules of solids are shown as cubes (Haidar andAbraham, 1991, cited by Krnel et al, 1998). Other studies have shown misconceptions of high school students related to the shape, size, weight, and animism of atoms (Griffiths and Preston, 1992).…”
Section: Coverage Of Conceptsmentioning
confidence: 99%
“…Although atomic and molecular structures and behaviours explain a plethora of chemical and lot of physical phenomena, students have difficulties understanding many concepts related to gases, liquids and solids (Krnel et al, 1998;Mullet and Gervais, 1990;Lee et al, 1993;BouJaoude, 1991;Domenech et al, 1993;Novick and Nussbaum, 1978;Benson et al, 1993;Krnel, 1994;Pereira and Pestana, 1991) and quantum concepts (Styer, 1996;Petri and Niedderer, 1998;Griffiths and Preston, 1992). For example, some drawings of high-school students show different forms of particles for different states of matter: gas molecules are round, molecules of liquids have irregular forms, molecules of solids are shown as cubes (Haidar andAbraham, 1991, cited by Krnel et al, 1998). Other studies have shown misconceptions of high school students related to the shape, size, weight, and animism of atoms (Griffiths and Preston, 1992).…”
Section: Coverage Of Conceptsmentioning
confidence: 99%
“…To adapt this categorization scheme to the alternative conceptions and misconceptions research, researchers added more categories. For example, Haidar and Abraham (1991) added alternative conceptions. Earlier, Renner, Brumby, and Shepherd (1981) added specific misconception.…”
Section: Scoringmentioning
confidence: 99%
“…A review of the literature shows that many students solve chemistry problems using algorithmic strategies and do not understand the chemical concepts on which the problems are based (cf. Abraham et al, 1992;Ben-Zvi et al, 1986;BouJaoude, 1992;Gabel et al, 1984;Garnett & Treagust, 1992;Griffiths & Preston, 1992;Haidar & Abraham, 1991;Hesse & Anderson, 1992;Linn & Songer, 1991;Mitchell & Kellington, 1982;Niaz & Robinson, 1992, 1993Novick & Nussbaum, 1978;Schmidt, 1992).…”
Section: Difference Between Algorithmic and Conceptual Problemsmentioning
confidence: 99%